Spatial Range of Secondary Education on the Example of Poznan - Walaszek , Marzena (Studia Oeconomica Posnaniensia, 2016)
The aim of this article is to present the results of studies of the spatial range of secondary schools in Poznań and the possibility of using this type of research in the procedure of delimitation of urban functional areas. The survey was conducted in 2013 by the Center for Metropolitan Research of Adam Mickiewicz University in Poznań, in 60 public and 3 private secondary schools, which contributed to a high research sample. The results of the study are a valuable source of information about the territorial origin of secondary school students, and the direction and intensity of commuting to schools reflects the importance and significance of an urban center.